كاریگه‌ری به‌رنامه‌یه‌كی فێركاری له‌سه‌ر بنه‌مای بیركردنه‌وه‌ی داهێنه‌رانه‌ بۆ گه‌شه‌پێدانی پاڵنه‌ری به‌ده‌ستهێنان لای خوێندكاران له‌‌ بابه‌تی داڕشتنی وێنه‌كێشان - نعمت, پ.د.جواده‌; خسره‌و, ئاكۆ حمه‌ (Sulaimani Journal for Humanities, 2023)
This research is entitled “The Impact of an Instructional Program Based on Creative Thinking on Developing Students’ Achievement Motivation in Composition of Painting”. In this study, a semi-experimental method has been used. The first aim of the study is revealing the impact of the instructional program on developing students’ achievement motivation in the subject of composition of painting. The second aim is revealing the difference between the two genders (male and female) on developing achievement motivation. An instructional program was created under the light of the scientific books, articles and experts’ experiences. The instructional program consisted of 12 instructional lessons. The population of the study consisted of 18 students (12 boys and 6 girls) who were students of Chamchamal Fine Arts Institute. They were all students of Plastic Department, Painting Branch in the subject of composition of painting; and they were in one group. The program lasted for 6 weeks in which the psychometric characteristics of the tool were utilized. A pre-test was utilized for the experiment and applied on the population. Finally, the participants took the post-test. Moreover, the data gained has been worked on through employing the statistical program of (Mann Whitney U test, Wilcoxon Test); that is to analyze the data gathered. The study reached the following findings: The experiment had positive impact on developing achievement motivation of the students in subject of composition of painting, Both genders benefited from the experiment and there was not a statistical difference between the achievements of both genders. Key Words: Painting Composition, Creative Thinking, Achievement Motivation.
Keywords: Key Words: Painting Composition; Creative Thinking; Achievement Motivation